Post-event behavioural intentions of participants in a women-only mass participation sporting event. (1st January 2012) - Crofts, Catherine; Dickson, Geoff; Schofield, Grant; Funk, Daniel
Little is known about the long-term physical activity (PA) behaviours of women after participating in a non-elite mass participation sporting event (MPSE). Three months post-event, 95 women reported their intentions to participate in: 1) the same event the following year; 2) other triathlons and/or other MPSE. The results suggest a strong association between the psychological connection model (PCM) and behavioural intentions. Most women with low intentions to repeat the event were in attraction while most women with high intentions to return were in attachment. These results show that, in addition, to providing short-term inducement for increased PA, short-distance MPSEs have the potential to act as 'gateway' events for other MPSE.